Learning Module Based on Verses About the Water Cycle in the Qur'an for Elementary School Students - Asmaul Husna; Muhaemin Muhaemin (IAIN Palopo, 2022)
This research is about the Development of verse-based learning modules about the water cycle in the Qur'an. The goal is to find out: 1) How is the initial prototype of the verse-based learning module about the water cycle in the Qur'an at SDN 50 Bulu Datu in class V students, and 2) How is the validity of the verse-based learning module about the Water Cycle in the Qur'an at SDN 50 Bulu Datu in grade V students. This research is a Research & Development (R&D) research, using the ADDIE development model which only uses three stages, namely: the analysis stage, the design stage, and the development stage. This research was conducted by SDN 50 Bulu Datu located on Jl. Kakatua, Prumnas Rampoang, Kec.Bara, Palopo City. The subjects of the study were class V students totaling 30 people. Data collection techniques in this study are: observation, documentation, interviews, validation. The result of this study is that the Water Cycle learning module is based on verses in the Qur'an by the three validators with several revisions through comments and suggestions from validators. Shows that, validity such as language is 80% valid, then the validity of the material, which is around 86% of categories, is very valid, while the design of the Water Cycle learning module, which is 90% of categories, is very valid.